In Vitro Screening for Cytotoxic Effect of Pore Forming Colicin N and Its Domains on Human Cancer Cells - Methawee Duangkaew,; Wanatchaporn Arunmanee, (Tropical Life Sciences Research, 2022)
Protein-based drugs have increasingly become an important segment of cancer treatment. In comparison with chemotherapy, they offer high efficacy and fewer side effects due to specifically targeting only cancer cells. Monoclonal antibodies are currently the main protein-based drugs in the market but their complexity and limitations in tumour penetration led to the development of alternative protein therapeutics such as pore-forming toxins. Colicin N (ColN), a pore-forming protein produced by E. coli, was previously found to exhibit cytotoxicity and selectivity in human lung cancer cells with promising potential for further development. Here we aimed to screen for the cytotoxicity of ColN in breast (MCF-7 and MDA-MB-231), lung (A549) and colon cancer cells (HT-29 and HCT-116) by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay with various concentrations for 72 h and to investigate the cytotoxic effect of ColN domains on cancer cells. It showed that ColN mildly mediated the decrease in cell viability except for MCF-7. The highest effect was seen in A549 and HCT-116 cells which showed 31.9% and 31.5% decrease in cell viability, respectively. The mild inhibition or promotion of cancer cell proliferation by ColN tend to be based on the cell types. Furthermore, to search for the functional domain of ColN used for cytotoxicity, full-length ColN and truncated ColN with deletion of translocating, receptor binding and pore-forming domains were also tested on HCT-116 colon cancer cells. The findings indicated that HCT-116 cells were not significantly sensitive to ColN but full length ColN caused slight decrease in cancer cell viability. The data in this study will benefit the further development of ColN for alternative protein-based cancer therapy.